Multi-vitamin supplementation blunts the circulating IL-6/IL-10 ratio increase after knee arthroplasty: A randomized, double-blind, placebo controlled study - Barker, Tyler; Henriksen, Vanessa T.; Rogers, Victoria E.; Trawick, Roy H.; Momberger, Nathan G.; Lynn Rasmussen, G. (Cytokine (Philadelphia, Pa.), 2021)
•Multi-vitamin supplement increased circulating vitamins C, D, and E before surgery.•Post-surgery vitamin C, D, and E decreases were mitigated with a multi-vitamin.•The serum IL-6/IL-10 increases after surgery were blunted with a multi-vitamin. Circulating interleukin (IL)-6 and IL-10 concentrations can be elevated following the surgically induced trauma of total knee arthroplasty (TKA). An exaggerated increase in IL-6 relative to IL-10 (i.e., IL-6/IL-10 ratio) associates with trauma severity and indicative of pro-inflammatory predominance. Although various vitamins and minerals alter individual IL-6 and IL-10 concentrations in the blood, surprisingly, it is unknown if a multi-vitamin supplement alters the IL-6/IL-10 ratio during the systemic inflammatory response following TKA. The objective of this study was to identify if a multi-vitamin with mineral supplement taken prior to alters the circulating IL-6/IL-10 ratio following total knee arthroplasty (TKA). This study consisted of a randomized, double-blind, placebo controlled design. Twenty-one subjects undergoing elective, primary, unilateral TKA were randomly assigned to a placebo (PL, n = 11) or multi-vitamin with mineral supplement (MV, n = 10). Supplements were taken daily starting approximately 6-weeks prior to surgery. Supplements were not taken the day of surgery or during inpatient care 2-days after surgery. Circulating IL-6, IL-10, high-sensitivity CRP (hsCRP), vitamin C (ascorbic acid (AA)), vitamin D (25-hydroxyvitamin D (25(OH)D)), and vitamin E (α-tocopherol (αT)) concentrations were measured in fasting blood draw samples obtained ~6-weeks prior to surgery (and before starting supplementation), the morning of surgery, and 24-hours and 48-hours after surgery. MV supplementation tended to increase serum 25(OH)D and significantly increased plasma AA and plasma αT before surgery without mitigating the post-operative IL-6 and hsCRP increases. However, the post-operative increase in the serum IL-6/IL-10 ratio after surgery was significantly blunted in the MV group. Based on these findings, we conclude that a multi-vitamin with mineral supplement taken daily for several weeks before surgery might reduce the pro-inflammatory predominance after TKA. Future research confirming or refuting the novel data presented herein is needed.